Knowledge, attitude and practice towards plastic pollution among residents in a rural area of Trivandrum district - Varghese, Meera; Suresh, Swathy; Vijayan, Vaishnavi Kattihara; Thodumannil, Vaishnavi; Kumar, Aditya; Muraleedharakurup, Jishnu (International Journal Of Community Medicine And Public Health, 2025)
Background: Plastic pollution has emerged as one of the most significant environmental challenges, with severe impacts on ecosystems, wildlife, and human health. Knowledge on microplastics and their long-term effects, remains limited in some regions. Many individuals still perceive plastic waste management as primarily a governmental or corporate responsibility, rather than a personal one. Although some individuals actively engage in reducing plastic consumption and participating in recycling initiatives, a large portion continues to rely on single-use plastics due to convenience, cost, and a lack of accessible alternatives. Hence this study aims to explore the level of knowledge, attitude and practice (KAP) towards plastic pollution among residents of rural area of Trivandrum district. Methods: A cross-sectional study was done among 246 study participants through convenience sampling. A semi structured questionnaire containing sociodemographic and KAP were prepared in kobo toolbox were used to collect the data. Data was analysed using SPSS software 25. Results: Among the 246 study participants 37% were having good knowledge, 50% were having good attitude and 41% were having good practice. Majority that is 55% of the participants were of age between 18-30 years, 60% were females, 40% had education status upto higher secondary. The association with ration card colour with level of knowledge and attitude and gender with practice were found to be statistically significant. Conclusions: There is a need to increase the level of KAP towards plastic pollution to achieve a plastic free society.